Aplikasi Operasional Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) di Politeknik PalComTech - Rini, Arsia (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2019)
Institute for Research and Community Service (LPPM) Politeknik PalComTech Palembang is an institution with carrying out tri dharma of college. LPPM Politeknik PalComTech manages several operational activities such as processing administration data of researchÂ and dedication for Manajemen Informatika, Akuntansi, and Desain Komunikasi Visual study programs. Operational activities carried out by LPPM Politeknik PalComTech still use simple data processing applications such as spreadsheet applications to complete all activities. The process of administration and storage is still done offline, so data synchronization between the head of LPPM and LPPM staff often gets constraints such as differences in data and reporting of research and service data, so it is necessary to develop an Operational Application for Research and Community Service at Politeknik PalComTech. This application applies a spiral method and is built to assist the LPPM division in processing of operational data at Politeknik PalComTech Palembang. LPPM, operational, palcomtech, administration.Keywords- LPPM, operational, Palcomtech, administration.